ANALISIS TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE RGEC DAN DAMPAKNYA TERHADAP PENINGKATAN JUMLAH NASABAH - Devika Cherly Putrihadiningrum (GREENOMIKA, 2021)
Covid-19 has an impact on the weak economy of the community, banking sector is a sector that helps improve the economy of the community in the midst of the covid-19 pandemic. The level of health of the bank is in the interests of all relevant parties, both owners, bank administrators, community users of bank services, Bank Indonesia applies bank supervision authority or other parties. If the bank's assessment is declared "healthy" or "very healthy", it will have an impact on increasing the number of customers be it the number of deposit customers, financing or services. The sample used in this investigation is financial dataPT. Bank Mandiri 2016-2020. The purpose of this study was to find out the influence of Risk Profile, Good Corporate Governance, Return on Asset, and Capital Adequacy Ratio on the increase in the number of customers at Bank Mandiri. The sample used in this study is the financial data of PT. Bank Mandiri 2016-2020. Data usage technique is to use SPSS. Based on the RGEC Test against Bank Mandiri it is known that Bank Mandiri's performance in 2016-2017 has excellent Risk Profile, Good Corporate Governance, Return on Asset, and Capital Adequacy Ratio values. This study shows that risk profile, good corporate governance, return on asset, and capital adequacy ratio have an effect both partially and simultaneously on the increase in the number of employees in independent banks.